2013
DOI: 10.1538/expanim.62.255
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Circulating CD11b<sup>+</sup>Gr1<sup>+</sup> cells and Recruitment into the Synovium in Osteoarthritic Mice with Hyperlipidemia

Abstract: Although recent studies suggest that hyperlipidemia is a risk factor for osteoarthritis (OA), the link between OA and hyperlipidemia is not fully understood. As the number of activated, circulating myeloid cells is increased during hyperlipidemia, we speculate that myeloid cells contribute to the pathology of OA. Here, we characterized myeloid cells in STR/Ort mice, a murine osteoarthritis model, under hyperlipidemic conditions. Ratios of myeloid cells in bone marrow, the spleen, and peripheral blood were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…C57BL/6J and STR/Ort mice were killed by deep anaesthesia and skin was then removed for the harvesting of ST with a scalpel. The harvested ST was digested with 1 mg/ml type I collagenase for 2 h at 37 °C . Perigonadal fat was also harvested from mice and was digested with collagenase D solution (2 mg/ml) (Roche Diagnostics, Indianapolis, IN) for 1–1·5 h at 37 °C .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C57BL/6J and STR/Ort mice were killed by deep anaesthesia and skin was then removed for the harvesting of ST with a scalpel. The harvested ST was digested with 1 mg/ml type I collagenase for 2 h at 37 °C . Perigonadal fat was also harvested from mice and was digested with collagenase D solution (2 mg/ml) (Roche Diagnostics, Indianapolis, IN) for 1–1·5 h at 37 °C .…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies have revealed that STR/Ort mice display human hyperlipidaemic-like symptoms, including high serum total cholesterol and triglyceride and hyperinsulinaemia [25,26]. Recently, we reported that myeloid cell populations are increased in the peripheral blood and spleen of STR/Ort mice, and are also recruited into ST [6]. Therefore, characterization of macrophage populations in ST and AT in STR/Ort is expected to provide insight into the relationship between OA pathology and hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the variable onset and progression compared with induced models of OA may necessitate greater animal numbers to sufficiently power studies to detect therapeutic effect, and longer treatment times for prophylactic studies and thus more test compound and cost. It is also important to recognize that the underlying mechanisms that drive the onset and progression of spontaneous OA in these animals are not well defined, and may reflect specific subtypes of idiopathic human OA - for example, early SCB remodeling, meniscal ossification and ligament changes in Hartley guinea pigs [ 114 – 117 ] and systemic inflammatory/immune response in STR/Ort mice [ 118 , 119 ].…”
Section: Is the Model Useful For Studying Prophylactic Strategies Or mentioning
confidence: 99%
“…STR/Ort mice are a well-characterized OA model that spontaneously develop OA with a progression resembling that of humans [ 22 24 ]. Synovial hyperplasia is also observed in STR/Ort mice [ 25 ], and we previously showed that the CD11b+ macrophage population in ST STR/Ort mice is higher than that found in C57BL/6J mice [ 17 , 18 ]. In addition, we reported that compared to synovial fibroblasts (CD11b−), synovial macrophages produce high levels of IL-1 β and TNF- α in STR/Ort mice [ 18 ].…”
Section: Introductionmentioning
confidence: 99%